Combined tube cystostomy and urethrotomy for the treatment of urethral obstruction due to urolithiasis in goats. Issue 2 (11th October 2019) - Applegate, Tanya J.; Barrell, Emily A.; Hassel, Diana M.; Hackett, Eileen S.; Simpson, Katharine M.; Callan, Robert J.
Abstract: Objective: To describe the treatment of goats with urethral obstruction secondary to urolithiasis by combining tube cystostomy and urethrotomy. Animals: Eight male goats. Study design: Short case series. Methods: Medical records (September 2012–September 2017) of male goats treated for obstruction secondary to urolithiasis with tube cystostomy and urethrotomy were reviewed. Data collected included signalment, history, physical examination findings, diagnostic results, perioperative treatments, operative details, hospitalization duration, intraoperative and postoperative complications, urolith analysis, and time to restoration of urethral patency. Long‐term follow‐up (>12 months) was obtained by email or telephone interviews of owners or by clinical examination. Results: Seven of eight goats were castrated males of various of breeds. All goats were tachycardic with urethral pulsation at admission. Uroliths were composed of calcium carbonate in four goats and silica in one goat. All goats regained urethral patency during hospitalization, and all were discharged alive from the hospital. Seven goats were alive at long‐term follow‐up. Postoperative complications included persistent urethral obstruction requiring a second urethrotomy 2 days postoperatively, premature dislodgement of the bladder catheter and jejunal obstruction secondary to adhesions, and recurrence of obstructive urolithiasis within the proximal perineal urethra requiring a second surgery 8 months later (1 each). Long‐term outcome was good, with urethral patency beyond 12 months in six of eight goats. Conclusion: Combining tube cystostomy and urethrotomy restored urethral patency in goats with urethral obstruction from uroliths. Although none of the complications seemed directly related to the urethrotomy, formation of abdominal adhesions and recurrence of urolithiasis affected long‐term outcomes. Clinical significance: Uroliths that do not dissolve in acidic urine may be more frequent in some practices. The combined approach of tube cystostomy and urethrotomy appears to successfully restore urethral patency with promising long‐term outcomes.